2011
DOI: 10.1128/jcm.02330-10
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cases of Clostridium difficile Infection (CDI) Presenting at an Emergency Room: Molecular and Clinical Features Differentiate Community-Onset Hospital-Associated and Community-Associated CDI in a Tertiary Care Hospital

Abstract: Definition of community-onset, hospital-acquired Clostridium difficile infection (CO-HA-CDI) is difficult in patients presenting with diarrhea at hospitals or outpatient clinics, especially 4 to 12 weeks after the last discharge. We performed C. difficile stool culture for 272 diarrheic patients visiting the emergency room (ER) between January 2006 and June 2010. C. difficile was isolated from 36 cases (13.2%), and isolation rates increased year by year, from 10.1% in 2008 to 12.4% in 2009 and 16.7% in 2010. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
3
11
1
Order By: Relevance
“…Our results demonstrated that the few cases of CA-CDI encountered in Kuwait occurred in a wide range of younger adult patient population of 18e65 years, without previous admission to hospitals. This is an observation similar to other studies on CA-CDI in which a much larger population of symptomatic patients was encountered in Europe and Southeast Asia [4,5,11,33]. Stratification of patient ages showed that the majority of our patients (62.5%) were young adults between 18 and 65 years, followed by those <18 years and finally those above 65 years.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results demonstrated that the few cases of CA-CDI encountered in Kuwait occurred in a wide range of younger adult patient population of 18e65 years, without previous admission to hospitals. This is an observation similar to other studies on CA-CDI in which a much larger population of symptomatic patients was encountered in Europe and Southeast Asia [4,5,11,33]. Stratification of patient ages showed that the majority of our patients (62.5%) were young adults between 18 and 65 years, followed by those <18 years and finally those above 65 years.…”
Section: Discussionsupporting
confidence: 85%
“…001, 002, 005, 015, 016, 023, 027, 064, 078 and 106 ribotypes in this study. Typing studies have shown that CA-CDI isolates have diverse molecular epidemiology with similarities and differences from hospital-acquired CDI strains (HA-CDI) [33,34,36]. Some studies have demonstrated that ribotype 027 is associated with CA-CDI more than HA-CDI [6], while other studies showed that ribotype 027 is seen more often with HA-CDI [37,38].…”
Section: Discussionmentioning
confidence: 98%
“…Contact precautions-EDs frequently care for patients infected or colonized with multidrug-resistant organisms (MDRO) including methicillin-resistant Staphylococcus aureus (MRSA), [87][88][89][90][91] vancomycin-resistant Enterococcus (VRE), 87,91 and a growing number of multidrug-resistant Gram-negative bacteria (e.g., Acinetobacter baumannii, Pseudomonas aeruginosa, and various Enterobacteriaceae). 92 Clostridium difficile 93,94 and other enteric pathogens 95 are likewise commonly encountered in patients with diarrheal illness. Transmission of these pathogens and others, including SARS and highly pathogenic influenza, can occur through direct contact with patients or their immediate surroundings.…”
Section: Transmission-based Precautionsmentioning
confidence: 99%
“…One study found that the proportion of community-acquired CDI (CA-CDI) among all CDI cases within a Busan hospital was 7.1% [25], while another reported that 59.4% of cases of CDI presenting at the emergency department of a Seoul hospital were community-acquired [26]. …”
Section: Introductionmentioning
confidence: 99%